Human papillomavirus (HPV): making the case for 'Immunisation for All'. (29th August 2016) - Prue, G; Lawler, M; Baker, P; Warnakulasuriya, S
Abstract : Human papillomavirus (HPV) contributes to the most common sexually transmitted infections, with repeated and persistent infection with particular types causing disease in both men and women. Infection with low‐risk HPV types can lead to genital warts and benign lesions of the oral cavity, while high‐risk types can cause various HPV‐related malignancies. The incidence of head and neck cancers has been rising in the past number of decades mostly due to oropharyngeal cancer linked to HPV infection. HPV vaccination has been shown to be effective for cervical and other anogenital HPV‐related cancers, and there is significant potential for HPV vaccination to prevent oropharyngeal cancers, given that the HPV types implicated in this disease can be protected against by the HPV vaccine. Few countries have implemented a universal HPV vaccination programme for males and females, with many countries arguing that female‐only vaccination programmes protect males via herd immunity and that men who have sex with men will be protected via targeted vaccination programmes. We argue these may be limited in their effectiveness. We propose that the most effective, practical, ethical and potentially cost‐effective solution is universal HPV vaccination that might lead to control of HPV‐related diseases in men and women alike.